Application of hybrid MCGDM model combined with VIKOR method in power grid equipment optimization. Issue 1 (July 2020) - Yang, Yatang; Sun, Gang; Liu, Yansong; Chen, Fumin
Abstract: The evaluation index of national grid equipment procurement source value system has multi-dimensional, multilateral and multi-attribute characteristics which can cause problems, in order to solve these problems and find out optimize grid equipment suppliers, this paper put forward a hybrid multi-criteria group decision-making (HMCGDM) model combined with VIKOR algorithm. Firstly, constructing the index stereo network and introducing the intuitionistic fuzzy number (IFN) into the model in order to avoid the hard division of the decision judgment matrix. Secondly, using the ANP algorithm to calculate the joint-edge relationship value of each index at individual layers, and constructing the weighted super matrix to calculate the subjective weight value of the bottom indexes. Then, calculating the objective weight value of the bottom evaluation index by using Entropy method, and combining it with the subjective weight value to modify the overall weight value. Finally, using the VIKOR algorithm to rank the alternative programmes, and making comparison with the model formed through the TOPSIS method. The results show that the VIKOR algorithm can calculate the weight values of the bottom indexes in the complex relational network objectively and effectively, and having a good applicability for the equipment optimization.